Gender understanding and sex role preference in four cultures - Munroe, Ruth H.
A scale of gender understanding and a measure of sex-role preference were administered to 3- to 9-year-old children from four traditional communities in Belize, Kenya, Nepal and American Samoa. Overall, findings reflected the strong contribution of cognitive development to the growth of gender understanding
Keywords: Sex roles